1976
DOI: 10.1111/j.1365-2265.1976.tb01964.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Pituitary‐testicular System With Age

Abstract: In order to provide a comprehensive account of pituitary-testicular function in man, 466 subjects, ranging in age from 2 to 101 years, were studied to examine blood levels of the pituitary gonadotrophins (LH and FSH), the sex steroids testosterone and oestradiol, the binding capacity of the sex hormone binding globulin (SHBG), the free testosterone and oestradiol fractions, and the transfer constant for the peripheral conversion of testosterone to oestradiol. The results were compared with clinical indices of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
5
3

Year Published

1982
1982
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(118 citation statements)
references
References 73 publications
9
101
5
3
Order By: Relevance
“…Until recently little attention has been paid to the role of estrogens in elderly men. The studies which have been reported so far show no change of total E 2 levels with age in men (1, 9, 28), or a decrease of E 2 levels only in old age (29,30). In the present study no changes with age were found.…”
Section: Discussioncontrasting
confidence: 55%
“…Until recently little attention has been paid to the role of estrogens in elderly men. The studies which have been reported so far show no change of total E 2 levels with age in men (1, 9, 28), or a decrease of E 2 levels only in old age (29,30). In the present study no changes with age were found.…”
Section: Discussioncontrasting
confidence: 55%
“…Similar declines were noted in salivary testosterone measurements (Read et al, 1981). Slight elevations in FSH and LH levels also suggest some degree of age-related testicular insensitivity (Baker et al, 1976;Gray et al, 1991). Older males also lose diurnal patterns of testosterone secretion that are common in younger men (Bremner et al, 1983), although the physiological significance is unknown.…”
Section: Agingmentioning
confidence: 52%
“…In contrast to these findings, Sniffen, [139], as well as Sokal [140] observed no loss of Leydig cells with age, while Kothari and Gupta [141] reported total Leydig cell mass to be increased in testes from their older men. Besides, a number of studies have also shown impaired testicular responsiveness to hCG stimulation [103,104,133,[143][144][145][146] or to recombinant human LH [147,148] stimulation in aging men. Harman and Tsitouras [103], Nieschlag et al, [104], Rubens et al, [144], Nieschlag et al, [142], and Nankin et al, [146] all noted decreases in both the absolute and relative (i.e., ratio of stimulated to basal) testosterone responsiveness in elderly as compared to young men.…”
Section: Humansmentioning
confidence: 99%